Comparative study of simple smear, formalin ethyl acetate concentration and Parasep® faecal parasite concentration technique for identification of the parasite and opportunistic protozoa in stool specimen from HIV infected patients - สุวรรณวัฒนะ ภาวิตา (Disease Control Journal, 2013)
This Study aimed to compare the diagnostic yields for parasites and opportunistic parasites in stool samples using three methods: simple smear, formalin ethyl acetate concentration and Parasep® faecal parasite concentration. Two hundred stool samples of HIV-infected patients were collected for laboratory investigation at Bamrasnaradura Infectious Diseases Institute. The stool samples were observed under the light microscope by 3 methods using (1) direct wet smear, (2) iodine preparations and (3) modified Ziehl- Neelsen stain. The diagnostic yield for parasites and opportunistic parasites using Parasep® was higher than that of simple smear, formalin ethyl acetate concentration with the percentage of 10.5, 8.0 and 4.0, respec¬tively. The diagnostic yield for opportunistic parasites by modified Ziehl-Neelsen stain. The Parasep® and Simple smearwere higher than that of formalin ethyl acetate concentration with 10.0, 10.5 and 7.0, respec-tively. This study suggests that the Parasep® together with the standard simple smear can potentially enhance the laboratory reports for diagnosing protozoas and opportunistic parasites. The result indicates that Parasep® can be used to improve the diagnostic yields for protozoas and opportunistic parasites in stool samples.